The Use of Fourier Transform Infrared Spectroscopy for Quantification of Adulteration in Virgin Walnut Oil - Pengjuan Liang; Hao Wang; Chaoyin Chen; Feng Ge; Diqiu Liu; Shiqi Li; Benyong Han; Xianfeng Xiong; Shenglan Zhao (Journal of Spectroscopy)
Currently, the authentication of virgin walnut oil (VWO) has become very important due to the possible adulteration of VWO with cheaper plant oils such as soybean oil (SO), puer tea seed oil (PO), and sunflower oil (SFO). Methods involving Fourier transform infrared (FT-IR) spectroscopy combined with chemometric techniques (partial least square) were developed for quantification of SO, PO, and SFO in VWO. IR spectra of oil samples were recorded at frequency regions of 4000–650 cm−1 on horizontal attenuated total reflectance (HATR) attachment of FT-IR. PLS model correlates the actual and FT-IR estimated values of oil adulterants (SO, PO, and SFO) with coefficients of determination (R2) of 0.9958, 0.9925, and 0.9952, respectively. The obtained RMSEC values of SO, PO, and SFO in VWO are 1.35%, 1.85%, and 1.43% (v/v), respectively. The method, therefore, has potential as a rapid method for quantification of product adulteration.